1994
DOI: 10.1177/101053959400700302
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Health in Urban Sabah, Malaysia: A Comparison of Citizens and Migrants

Abstract: This paper describes selected maternal and child health indicators based on a cross-sectional study of citizens and migrants in Sabah, Malaysia. A total of 1,515 women were interviewed from a multi-stage random sample of households in eight urban centers. Among the 1,411 women in the sample who had experienced a pregnancy before, 76% were local citizens and 24% were migrants. There were statistically significant differences between citizens and migrants in ethnicity, religion, education, household income, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
2
6
0
2
Order By: Relevance
“…Nearly one in ten children in Bangladesh die before reaching the age of five. A similar pattern has been found when examining the use of health services among migrant and non-migrant groups (Bender et al, 1993;Tam, 1994;Zulkifli et al, 1994). The child survival advantage associated with urban residence in contemporary developing countries is documented in a large body of demographic literature (Davis, 1973;Behm & Vallin, 1982;Hobcraft et al, 1984).…”
Section: Introductionmentioning
confidence: 52%
“…Nearly one in ten children in Bangladesh die before reaching the age of five. A similar pattern has been found when examining the use of health services among migrant and non-migrant groups (Bender et al, 1993;Tam, 1994;Zulkifli et al, 1994). The child survival advantage associated with urban residence in contemporary developing countries is documented in a large body of demographic literature (Davis, 1973;Behm & Vallin, 1982;Hobcraft et al, 1984).…”
Section: Introductionmentioning
confidence: 52%
“…Migrants were often reported to utilise ANC to a significantly lesser extent than either the natives or longer‐settled migrants (Zulkifli et al . ). Based on a systematic review, Heaman et al .…”
Section: Discussionmentioning
confidence: 97%
“…One study in Malaysia found that while few migrant women never received any prenatal care during their pregnancy, they tended to initiate prenatal care as late as 7 months compared to local citizens starting prenatal care early in the first trimester [37]. Another study of migrant women in India indicated that only 37% of rural to urban migrants had adequate prenatal care and that recent migrants had prenatal visits significantly less than those who were more settled (35% VS. 39%) [38].…”
Section: Discussionmentioning
confidence: 99%